EXPLORING LANGUAGE OF BUSINESS NEGOTIATIONS (A CASE STUDY AT CV ARAYAH INDO TEKNIK MAKASSAR) - Andi Rayyan Samtidar; Andi Samtidar (Bahasa Inggris Program Sarjana Terapan, Universitas Negeri Makassar, 2023)
The aims of this research were to investigate the tactics of negotiations applied and explore the language usage by the top managerial officers of CV Arayah Indo Tehnik Makassar that they experienced during their business negotiations. This research applied a case study to achieve the research objectives. The instrument used in the data collection were questionnaire and semi-structured interview. The subjects of this research, the board of directors CV Arayah Indo Tehnik Makassar, were taken using purposive sampling technique. The questionnaire was distributed to and filled out by the main director of CV Arayah Indo Tehnik Makassar. The interview sample was conducted also to the main director CV Arayah Indo Tehnik Makassar. The results of this study found that all 15 strategies of business negotiations and 6 language sample of business negotiations were utilized during their practical business negotiations. However, the utilizations of those 15 tactics and language of negotiations were based on practical rather than theoretical knowledge